(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
Cleft lip and palate (CLP) is one of the most common craniofacial anomalies and may cause significant alterations in airway morphology and function. The advent of cone-beam computed tomography (CBCT) has provided a reliable, low-dose, three-dimensional tool to assess upper airway dimensions in growing patients. This mini-review summarizes current findings on oropharyngeal airway characteristics in preadolescent patients with nonsyndromic unilateral and bilateral CLP. CBCT-based studies generally demonstrate reduced oropharyngeal volumes and altered airway morphology compared with non-cleft controls. Bilateral cases often show greater constriction than unilateral ones, although methodological heterogeneity limits definitive conclusions. Standardized imaging protocols, artificial-intelligence segmentation, and integration with functional tests such as polysomnography are needed to improve understanding and clinical translation.